PERANAN PENGADILAN AGAMA DALAM MENYELESAIKAN PERMOHONAN CERAI THOLAK MENURUT UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN - Dewi Ratnasari (Journal of Law ( Jurnal Ilmu Hukum ), 2016)
ABSTRACTThe title of this paper is the role of the court in resolving the divorce petition tholak according to Law No. 1 of 1974 on marriage .The formulation of the problem of how to reconcile the efforts of religious courts in the party who filed for divorce in a religious court tholaksamarinda and what the legal consequences of divorce tholak according to Law No. 1 of 1974. The purpose for doing this study to obtain information about the role of religious courts in resolving divorce petition tholak according to Law No. 1 of 1974 on marriage . Writing this thesis using empirical juridical library with study analysis and interview sources.Divorce in certain circumstances be considered the ultimate solution remains to drown out the bickering and discord in the household of husband and wife therefore be of a husband and wife running a live household carefully so that marriage really achieve the purpose of marriage itself , that forms the family the eternal happy and prosperous in the world and the hereafter . Then the husband and wife should help each other and complement so that each can develop his personality in addition to an obligation of marriage also has a close relationship with religion .Keywords : the role of religious courts in resolving divorce petition tholak according to the law No. 1 of 1974 About marriage